Human cultural tradition in human trafficking: Legal and cultural analysis in Indonesia - Wahyuda, Aisha Radha (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2024)
This paper explores the intricate interplay between legal frameworks and cultural norms regarding human trafficking in Indonesia. By examining the cultural dimensions inherent in the practice, it aims to provide a comprehensive understanding of the phenomenon. Through a multidisciplinary approach that integrates legal analysis and cultural studies, this research elucidates the ways in which traditional cultural practices intersect with contemporary legal structures, shaping the landscape of human trafficking in the Indonesian context. By identifying these intersections, the study seeks to contribute to ongoing efforts to combat human trafficking by fostering a nuanced understanding of its socio-cultural underpinnings.